Study on the durability of ultrasonically welded carbon fiber reinforced PA6 to AA6061 aluminum alloy joints - Haipeng Zhou; Yilong Zhang; Yufan Cai; Yuanduo Yang; Sansan Ao; Yang Li (Journal of Materials Research and Technology)
In this study, 6061 aluminum alloy (AA6061) and carbon fiber reinforced PA6 (CF/PA6) hybrid structure was fabricated using ultrasonic welding. The AA6061 was modified by KH550 silane coupling agent (SCA), and a PA6 interlayer was prepared on the AA6061 surface as the energy director (ED). The introduction of SCA enhanced the chemical bonding between AA6061 and CF/PA6, forming plenty of Al–O–Si chemical bonds at the welding interface. During the ultrasonic welding process, the molten resin thoroughly wetted the aluminum alloy surface, forming a strong mechanical interlocking. The maximum tensile-shear strength of the AA6061-CF/PA6 ultrasonically welded joint was 30.2 MPa, and the interfacial failure mode was mixed failure. Afterward, the durability of AA6061-CF/PA6 ultrasonically welded joints was investigated from three aspects: post welding heat treatment (PWHT), thermal cycling shock, and salt spray test. The AA6061-CF/PA6 hybrid joints maintained a tensile-shear strength around 30 MPa for different PWHT temperatures, and over 20 MPa after 12 thermal cycles and 15 days of salt spray test.